Percutaneous ablation of functioning adenoma in a patient with a single adrenal gland. (3rd June 2013) - Nunes, Thiago Franchi; Szejnfeld, Denis; Xavier, Ana Carolina Wanderley; Goldman, Suzan Menasce
Abstract : The conventional treatment of functioning adrenal adenomas is laparoscopic resection. Since the 1990s, radiofrequency ablation has been increasingly applied to the treatment of tumours of the liver, lungs and musculoskeletal system. However, the use of radiofrequency ablation to treat adrenal nodules is still an uncommon procedure, particularly in aldosterone-producing adenomas. We report the case of a 35-year-old male patient with resistant hypertension, hypokalaemia and aldosterone-producing adenoma in a single adrenal gland. The patient underwent CT-guided percutaneous radiofrequency ablation. Clinical, laboratory and MRI follow-up data indicated excellent response to treatment. This case report is the first in the literature to describe the use of CT-guided percutaneous radiofrequency ablation in the treatment of a functioning adrenal adenoma in a patient with a single adrenal gland.